(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
Detailed textural study of the Northern section of the Syrian Continental shelf (N35.92991 E35.91785: N35.35752 E35.91542) has been carried out in order to determine the sediment nature and distribution. The sediments are mainly coarse to very fine-grained particles, moderately sorted, negatively skewed to fine skewed and leptokurtic to mesokurtic in nature. Interrelationship of various parameters shows bimodal nature of sediments having dominance of mainly medium to coarse sand. The major part of the sediment fall in coarse to very fine grained category (sand, silt and clay). Based on the CM (Coarser one percentile and Median size values in micron) pattern, the sediment fall in rolling and suspension field. These factors indicate that the sediments discharged from the rivers mixes with offshore sediments and with the sediments eroded from a source rock. Moreover, the wave energy conditions were high enough to disperse the sediments along the shelf and passing it to the open ocean and later dispersing them by littoral currents. أجريت دراسة ترسيبية مفصلة للقطاع الشمالي من الرصيف القاري السوري (N35.92991 E35.91785: N35.35752 E35.91542) بغية تحديد طبيعة، وتوزع وخصائص الرسوبيات البحرية الموزعة على كامل هذا القطاع. أظهرت الدراسة أن الرسوبيات تتراوح بين الخشنة والناعمة جداً، معتدلة الفرز، ذات ميل سلبي إلى متماثل وأخيراً مفرطحه إلى متوسطة التفرطح. أظهرت علاقات الارتباط المختلفة لعدة بارامترات الطبيعة ثنائية الترسيب لرسوبيات المنطقة حيث يغلب الرمل على كافة العينات مع وجود كل من السلت والغضار ولكن بنسب مختلفة. بالاعتماد على مخطط CM، فإن أغلب الرسوبيات قد ترسبت إما عن طريق الدحرجة على القاع أو بشكل مباشر من المعلقات. تشير هذه العوامل إلى أن الرسوبيات قد تم تفريغها من الأنهار ومن ثم اختلطت مع الرسوبيات العميقة والرسوبيات المجواة من الصخور الأم. علاوة على ذلك، كانت طاقة الأمواج عالية بما فيه الكفاية لتشتيت هذه الرواسب على طول الرصيف القاري السوري ومن ثم نقلها إلى الأعماق المفتوحة ليتم تفريقهم بعد ذلك من قبل التيارات الساحلية.